Azide-alkyne cycloadditions in a vortex fluidic device: Enhanced "on water" effects and catalysis in flow - Oksdath Mansilla, Gabriela (2021)
The Vortex Fluidic Device is a flow reactor that processes reactions in thin films. Running the metal-free azide-alkyne cycloaddition in this reactor revealed a dramatic enhancement of the "on water"effect. For the copper-catalyzed azide-alkyne cycloaddition, stainless steel or copper jet feeds were effective reservoirs of active copper catalyst.